The effect of camel milk on house dust mite allergen induced asthma model in BALB/C mice - Ayaulym Rakhmatulina; Shynar Kenenbay; Altynay Abuova; Maigul Kizatova; Akniyet Ibraikhan; Farrukh Makhmudov; Aitugan Mukashev; Aigerim Aitbaeva; Zhastalap Abilkaiyr; Galiya Ibadullayeva; Urishbay Chomanov; Akhmet Murzabulatov; et al. (PLoS ONE, 2025)
Camel milk has demonstrated robust immunomodulatory and anti-inflammatory properties in various clinical and experimental studies. However, no previous studies have characterized the cellular immunological effects of camel milk in the context of allergic asthma. Therefore, the present work aimed to evaluate the protective effects of camel milk in house dust mite induced asthma in mice, which emulate human pulmonary inflammation. Female BALB/c mice aged 8- to 10-week-old were intranasally sensitized with vehicle or HDM in 2.5 µl (5 µg) per nostril, 5 days a week for 3 weeks. On day 22, mice received an HDM challenge by a large volume but low dose into the lung (5 µg in 50µl) using intranasal inoculation. Using oral gavage technique, CM/HDM group mice received 0.5 ml of camel milk or vehicle five times a week, starting a day prior to sensitization. On day 23 following HDM challenge, mice were exposed to serial challenges with 10, 20, 40 and 100 mg/ml aerosolized methacholine to measure lung dynamics. Furthermore, BALF and whole lung samples were harvested to examine pulmonary inflammation. Camel milk effectively inhibited both HDM-induced infiltration of eosinophils and AHR. In addition to this, camel milk downregulates the number of pulmonary Th2 and Th17 cells and suppressed CCL17 expression in whole lung homogenates. Furthermore, camel milk reduced HDM-induced IL-4 and IL-13 expression following in vitro restimulation of pulmonary T cell subsets. Additionally, camel milk suppressed total concentrations of IL-5 and IL-13 in the lung. These results corroborate the asthma-preventive potential of camel milk and highlight the significance of diminished local concentrations of Th2- associated cytokines. In the present study, the observed downregulation of asthma progression by camel milk suggests its potential health benefits; however, further experimental and controlled clinical trials are needed before it can be considered a supplementary approach for allergic asthma management.